United Nations Peacekeeping Operations and the Challenge of Communal Violence in Host Communities: The Case of the United Nations Interim Security Force for Abyei (UNISFA) - Wol, Dhieu Mathok Diing (European Journal of Applied Sciences, 2024)
This paper examines the effectiveness of the United Nations (UN) peacekeeping operations in addressing communal violence in host communities, using the United Nations Interim Security Force for Abyei (UNISFA) as a case study. Despite UNISFA's presence, the Abyei region has experienced tragic events, such as the death murder of the Ngok Dinka Paramount Chief by Messiriya militia, which occurred in the presence of peacekeeping forces. The paper draws on opinions accounts from the local communities and the vast literature on the interventions that UNISFA undertook to curb the violence in host communities. It also takes accounts of community leaders who claim that UN peace keepers are at the core of local disputes in Abyei. This article adds to the existing literature by showing that is that the UNISFA has faced challenges in tackling conflicts at the boundaries. This was seen clear in the conflict between Nogk and Twic over Aneet and also in the case of the 14-Mile in Aweil North County between Dinka Malual and Riziegat tribe. Hence, the paper examines the issue of disputes over boundaries by the host communities. The paper presents policy recommendations to improve the performance of the UN peacekeeping missions in addressing communal conflicts in areas where they are deployed.